Analysis of the ŠKODA brand perceptions on different markets - Doležal, Jiří (2021)
Lately, brands are becoming increasingly important across all industries. Consumers are forming relationships with brands attributing brand building process a great significance. Automotive industry belongs to the most competitive industries with high brand loyalty attributing the brand even greater importance. This study focuses on a carmaker ŠKODA and perception of its brand between Czech, German and Finnish markets. In order to find the similarities and differences between the researched markets and provide future brand development, following objectives were set. First objective was to develop a theoretical framework integrating the brand equity components and the brand identity model on in-depth literature review, which serve as a basis for the empirical part. Second objective was to develop an overview regarding the branding benchmarks and current trends in the automotive industry. Thirdly, the objective was to analyze the three markets’ similarities and differences in brand perceptions of the case company ŠKODA based on the conducted survey and compare the results with previous studies. Lastly, based on the theory background, benchmarks, trends and conducted research, provide suggestions on how to improve brand perceptions of ŠKODA on researched markets. A quantitative research method, specifically an online questionnaire, has been chosen for this research. Total amount of 195 respondents from the three analyzed markets approached the questionnaire. However, not all respondents were admitted to participate in the research after the introductory question due to their possible influence on the findings which resulted in having 54 respondents from Czech Republic, 64 from Germany and 59 from Finland who fully completed the questionnaire. The research findings confirmed a strong position of ŠKODA brand on the Czech market, where perceptions predominantly surpassed the remaining markets.